Inadvertent higher rate atrial pacing after dual chamber pacemaker implantation - What is the underlying mechanism? - Arpita Katheria; Kamlesh Raut; Ankit Kumar Sahu; Aditya Kapoor (Indian Pacing and Electrophysiology Journal)
Unexplained change in parameters, despite good lead positions or odd ECG patterns following implant should lead to suspicion of lead swap, amongst other possibilities. An easy way to confirm this is by paying careful attention to device EGMs and recording the ECG by switching off one channel, and pacing single channel (in either AAI or VVI mode).